Application of simulated intestinal fluid on the phospholipid vesicle-based drug permeation assay - Fischer, Sarah Maud; Saal, Wiebke; Fricker, Gert (International journal of pharmaceutics, 2012)
The compatibility of fasted state simulated intestinal fluid (FaSSIF) in drug permeation studies employing the phospholipid vesicle-based permeation assay (PVPA) model was confirmed by a set of different integrity indicators. Neither calcein permeability nor electrical resistance were found significantly changed indicating unaffected barrier tightness. Furthermore, the release of phospholipid from the barriers in contact with FaSSIF was negligible, although sodium taurocholate disappeared from the donor - possibly due to transfer into the barrier. Visual examination of the barrier structure by confocal laser scanning microscopy (CLSM) revealed no changes. The model drugs, cimetidine, nadolol, ketoprofen and griseofulvin showed either slightly enhanced or unchanged permeability values in the presence of FaSSIF. This may be attributed to micellar encapsulation and/or slight changes in barrier characteristics. Particularly for poorly soluble drugs, FaSSIF appeared favourable in terms of markedly improved recovery. Moreover, utilisation of BSA in the receiver compartment seems to augment this beneficial effect on recovery rate. It is likely that this experimental set-up affords better sink conditions in the receiver phase, which results in higher fluxes. Overall, a combination of FaSSIF in the donor phase and BSA in the receiver phase facilitates improved experimental output.
Available online 17 October 2011
Gesehen am 12.07.2019